Wireless Sensor Network Technologies for the Information Explosion Era - Hara, Takahiro; Zadorozhny, Vladimir I.; Buchmann, Erik.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume aims to cover both theoretical and practical aspects related to this challenge, and it explores directions for future research to enable efficient utilization of WSNs in the information-explosion era. The book is organized in three main parts that consider (1) technical issues of WSNs, (2) the integration of multiple WSNs, and (3) the development of WSNs systems and testbeds for conducting practical experiments. Each part consists of three chapters.
Scheduling and Data Management -- Survey on Data Routing in Wireless Sensor Networks -- Energy-Efficient Task Scheduling and Data Aggregation Techniques in Wireless Sensor Networks for Information Explosion Era -- Secure Data Aggregation in Wireless Sensor Networks -- Networked Sensing Systems -- Data Management Solutions in Networked Sensing Systems -- Integration of Heterogeneous Sensor Nodes by Data Stream Management -- Stream-Based Real World Information Integration Framework -- Implementation and Development Support -- Toward Construction of Wearable Sensing Environments -- Applying Overlay Networks to Ubiquitous Sensor Management -- X-Sensor: Wireless Sensor Network Testbed Integrating Multiple Networks.
Keywords: Engineering; Artificial intelligence; Engineering mathematics; Telecommunication; Engineering; Appl.Mathematics/Computational Methods of Engineering; Communications Engineering, Networks; Artificial Intelligence (incl. Robotics).; Signal, Image and Speech Processing